Marketplace behaviour of Malaysian consumers - Ndubisi, Nelson Oly (Management research news, 2006)
Six varied papers on marketing issues in Malaysia - an interesting mix of research. Two papers address internet banking and consumers' attitudes to operating their accounts and financial business in this way. One paper looks at consumers' response to sales promotional tools and another at effects of gender on purchase decisions. The two final papers look at the influence of the family structure on purchase decisions and the ways in which Malaysian customers articulate their dissatisfaction. A useful adjunct for anyone looking to market in this region.